LIMBAH BATUBARA SEBAGAI BAHAN CAMPURAN PERBAIKAN LAPISAN TANAH DASAR DI KALIMANTAN SELATAN - Yasruddin Yasruddin; Utami Sylvia Lestari; Akhmad Rifqy (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The coal waste that is generated from the steam power plant (PLTU) process can cause environmental pollution. The coal waste is then investigated to be used as a mixture to stabilize the subgrade of road construction for the South Kalimantan area. The purpose of this study was to determine the characteristic value of each combination of fly ash, bottom ash, and cement as a mixture of subgrade layer. The 5 combinations of fly ash, bottom ash, cement, and soil were used as a mixture of subgrade layer. This research used an experimental method through laboratory testing which included the Atterberg limit testing, specific gravity, sieve analysis, compaction and california bearing ratio. Furthermore, it was obtained the composition of fly ash, bottom ash, cement and soil that can be used for common and selected embankments in highway construction for soft soils in South Kalimantan. Keywords: coal waste, subgrade, selected embankment, common embankment.